2004
DOI: 10.1007/s00701-004-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tumour volume and surgery on the outcome of adults with supratentorial WHO grade II astrocytomas and oligoastrocytomas

Abstract: Pre- and postoperative tumour volumes, and the involvement of more than one lobe were strongly associated with worse outcome. Preoperative tumour volume was the strongest predictor of OS (p<0.01) and the only predictor of MT (p<0.05). The absolute and relative volumes of tumour removed by surgery were not significantly associated with outcome. CONCLUSIONS. Initial tumour volume, measured as the volume of T2-hyperintensity on MRI, and tumour extension are the strongest predictors of outcome in patients with sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 28 publications
0
14
1
1
Order By: Relevance
“…Surgery continues to be the preferred treatment for most patients with low-grade gliomas (LGG). While some studies demonstrated that the extent of resection of LGG including OG favorably affects outcome [20][21][22][23][24] others did not confirm this finding [25][26][27][28].…”
Section: Radiological Follow-upcontrasting
confidence: 42%
“…Surgery continues to be the preferred treatment for most patients with low-grade gliomas (LGG). While some studies demonstrated that the extent of resection of LGG including OG favorably affects outcome [20][21][22][23][24] others did not confirm this finding [25][26][27][28].…”
Section: Radiological Follow-upcontrasting
confidence: 42%
“…A potential problem with our approach of measuring the tumor volume based on MRI [15] is that hyperintensity changes on T2-weighted and FLAIR images, especially in the long-term follow-up, can be side effects of radiation [5]. Even if postirradiation changes might interfere in the evaluation of tumor progression after RT in the long term, they should not influence the assessment of tumor response, which is characterized by a reduction of the T2-hyperintense, neoplastic regions relatively early after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…From our database of WHO grade II glioma patients [14,15] we selected those subjected to RT. The survival data were updated in March 2005 for all patients.…”
Section: Clinical and Volumetric Datamentioning
confidence: 99%
See 1 more Smart Citation
“…removal, as patients with more extensive tumor resection had significantly longer OS 11,[14][15][16]19,20 . Our data showed a very similar KPS at diagnosis between these two groups.…”
Section: Referencesmentioning
confidence: 99%